2D Materials: Large Out‐of‐Plane Second Harmonic Generation Susceptibility in Penta‐ZnS2 Sheet (Adv. Theory Simul. 6/2020). Issue 6 (5th June 2020) - Shen, Yiheng; Guo, Yaguang; Wang, Qian
Abstract : In contrast to conventional stoichiometric zinc sulfide, the ground state geometry of 2D ZnS2 is identified as a pentagonal sheet composed entirely of pentagons by Qian Wang in article number 2000027 through global structural search. Due to the lack of centrosymmetry and out‐of‐plane mirror symmetry in its geometry, this sheet exhibits giant out‐of‐plane second harmonic generation susceptibility, which is ≈2–3 orders of magnitude larger than that of Janus 2D materials, showing great promise for applications.